A Prospective Real-World Study of Bacillus clausii Evaluating Use, Treatment Habits and Patient Satisfaction in Italian Community Pharmacies: The PEGASO Study - Corrado Giua; Flora Romano; Enrico Keber; Paolo Pellegrino; Marcos Perez; Maria Chiara Uboldi; SIFAC group of clinical pharmacists (SGCP) (Adis, Springer Healthcare, 2023)
Abstract Background Ailments such as diarrhoea and antibiotic-associated gut symptoms are generally self-managed using probiotics. Real-world data on reasons behind self-medication with over-the-counter (OTC) products and patient-reported outcomes can be investigated strategically by the pharmacists. Objective This study evaluates the use of Bacillus clausii (Enterogermina®) at the Italian community pharmacies among self-medicating patients, their treatment habits and perceived benefits. Design This is a multicentre, prospective, non-interventional study which included two visits [at screening (T0) and end of the study (T1) when symptoms had subsided, ≤ 30 days from T0]. Patients who were already inclined to buy B. clausii were enrolled and instructed to complete a questionnaire at T0 and T1. The primary objective was to evaluate the reasons for taking B. clausii. Secondary objectives assessed treatment duration, perceived effectiveness, quality of life (QoL), treatment satisfaction and safety outcomes. Results Overall, 268 patients were enrolled; 99.6% of them were evaluated at T0 and 97.4% at T1, and safety was evaluated in 97.8% who had ≥ 1 dose of B. clausii. At T0, mean age was 50.7 years and majority were females (62.2%). In the interview, main reason stated for using B. clausii at T0 was diarrhoea (56.93%), followed by other gastrointestinal symptoms. Treatment duration was shorter in those with diarrhoea or abdominal pain versus those with constipation or abdominal tension. More than 90% perceived their symptoms to have improved or improved very much. Overall QoL improved in all the aspects measured. Treatment satisfaction was reported by nearly 90% of patients as satisfied, very satisfied or extremely satisfied. No adverse events were reported. Conclusion This is the first pharmacy-based study in Italy that evaluated the real-world usage of an OTC probiotic containing B. clausii among self-medicating adults. Diarrhoea was the most common reason for use, with high-level of perceived effectiveness and patient satisfaction with B. clausii.